Virtual Screening Of Protein Tyrosine Phosphatase 1b In Search For Natural Products With Potential Activity Againts Diabetes Mellitus Type 2 - Ho, Yueng Hsing (2018)
The world population of diabetes mellitus patients had reached 422 million in the year 2014 and projected to be the seventh leading cause of death in the year 2030 by World Health Organization. Type 2 Diabetes Mellitus (T2DM) was responsible for 90-95% of all diabetes and it had affected approximate 6% of the adult population in the western society. In Malaysia, the prevalence of T2DM had doubled from 8.3% (1996) to 17.5% (2015) in duration of ten years. Now, 1 out of 5 Malaysian are diabetic and with over 45% of overweight and obese population with 1 million obese children.